Tracheal injury detected immediately after median sternotomy by inexperienced surgeons: two case reports - Jun Takeshita (Journal of Medical Case Reports, 2018)
Abstract Background Although median sternotomy is standard during cardiac surgery, the procedure is associated with a risk of injury to mediastinal organs. Here, we discuss two cases of tracheal injury following median sternotomy during cardiac surgery. Case presentation Ventilation failure occurred in a 78-year-old Japanese man and a 71-year-old Japanese man after median sternotomy, and tracheal injury was identified. The sites of injury were directly repaired and covered with mediastinal fat tissue, following which ventilation was successful. The burn-like deposits observed at the site of tracheal injury and on the removed endotracheal tube support the notion that the injuries in our patients were caused by electrocautery prior to median sternotomy. In one case, short sternotracheal distance may have contributed to tracheal injury during post-sternal manipulation. In both cases, the relative inexperience of both surgeons also supports the suspected cause of injury. Conclusions Tracheal injury represents a potential complication following median sternotomy, especially when performed by inexperienced surgeons or in cases of short sternotracheal distance. Anesthesiologists should consider this rare yet potentially lethal complication.